Active inaction: why the climate crisis is a moral crisis. Issue 1 (2nd January 2023) - Rahman, Rafidah
ABSTRACT: Recently, climate change discussions have taken a distinct turn, with industrialised nations resolutely advocating a "just transition". However, how does that work when industrialised nations have not delivered on their $100 billion pledge to the global South? At COP26, many hoped for a climate fund to compensate poorer countries. In lieu of providing dedicated funds, rich countries requested more dialogue. This viewpoint discusses how this "active inaction" has led to a moral problem in the face of climate change. The viewpoint also explains how the global North is just as dependent on the global South, if not more when it comes to development. It provides a better understanding of the need for rich countries to create a separate loss and damage finance unit incorporating risk reduction, risk transfer, and social safety nets. The purpose of this viewpoint is to increase awareness that it is in the world's interest to protect poorer nations from climate change and that just transition and loss and damage should not be tradeoffs. Rather, loss and damage should precede a just transition. For a just transition to be possible, climate reparation needs to come first.